(untitled) (Journal of Technology and Operations Management, 2020)
The purpose of this paper is to study the relationship between consumer resistance to innovation like smartphone and perceived risk. This study was conducted by using self-administered questionnaire to seek the consumer behavior and their attitude towards innovation. This study indicates the significant positive causal relationship between resistance to innovation and perceived risk by consumers. The choice of research methodology and sampling technique minimized the sampling limitations in the study. This study contributed to the existing body of knowledge as well as in the current market. It gives the idea to the marketer and producer to enhance their product features to reduce the resistance to innovation.